2007
DOI: 10.2134/agronj2006.0361
|View full text |Cite
|
Sign up to set email alerts
|

Thatch and Mat Management in an Established Creeping Bentgrass Golf Green

Abstract: Thatch is a layer of partially decomposed organic matter between green shoot tissue and the soil surface, and mat is thatch partially intermixed with topsoil. Excessive thatch-mat layering (.2.54 cm) is generally detrimental to turfgrass management, and numerous techniques including various mechanical and topdressing regimes, have been attempted to reduce its severity. This factorial experiment investigated the effectiveness of combining mechanical-biological and topdressing treatments for controlling thatch-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(177 citation statements)
references
References 22 publications
1
158
2
Order By: Relevance
“…Spring-plus-summer coring resulted in increased chlorophyll levels as well as improved turf color and quality in late summer. Eggens, 1980;White and Dickens, 1984;Murphy et al, 1993;McCarty et al, 2005McCarty et al, , 2007. Murray and Juska (1977) observed that coring reduced total organic matter in the thatch of Kentucky bluegrass (Poa pratensis L.), but the eff ect was short-lived.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spring-plus-summer coring resulted in increased chlorophyll levels as well as improved turf color and quality in late summer. Eggens, 1980;White and Dickens, 1984;Murphy et al, 1993;McCarty et al, 2005McCarty et al, , 2007. Murray and Juska (1977) observed that coring reduced total organic matter in the thatch of Kentucky bluegrass (Poa pratensis L.), but the eff ect was short-lived.…”
Section: Introductionmentioning
confidence: 99%
“…× C. transvaalensis (Burtt Davy)]. The most extensive coring studies in creeping bentgrass were reported by McCarty et al (2005McCarty et al ( , 2007 and Murphy et al (1993). Murphy et al (1993) investigated the eff ects of hollow-and solid-tine coring on thatch-mat in a 'Penneagle' creeping bentgrass green.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate the greatest difference in soil physical properties was most prominent shortly after hollow tine or solid tine core cultivation; which diminished as roots grew, compaction dissipated, and core channels were covered or filled. Other researchers have reported greater air porosity and saturated water conductivity in turf managed with hollow tines compared to solid tines, and enhanced water infiltration in turf managed with hollow tine core cultivation compare to untreated turf (Murphy et al, 1992;Baldwin et al, 2006;McCarty et al, 2007).…”
Section: Turf: Golf Course Fairwaymentioning
confidence: 96%
“…As a result one would anticipate increased soil compaction with the solid tine cultivation and greater accessibility of soil adsorptive sites with the hollow tine cultivation. This would influence infiltration and hydraulic conductivity (Murphy et al, 1992;Baldwin et al, 2006;McCarty et al, 2007) as well as pesticide availability for transport (Liu et al, 1995;Gardner et al, 2000;Raturi et al, 2005). Analysis of pesticide loads with runoff volumes and pesticide concentrations in the runoff showed loads were attributed to runoff volume more than chemical concentrations for both management practices (volume r 2 = 0.78 to 0.90, concentration r 2 = 0.05 to 0.22).…”
Section: Wwwintechopencommentioning
confidence: 99%